2023
DOI: 10.1186/s12889-023-15894-3
|View full text |Cite
|
Sign up to set email alerts
|

Sleep duration trajectories and all-cause mortality among Chinese elderly: A community-based cohort study

Abstract: Background China is among the largest and fastest aging countries. The elderly population is more vulnerable, with higher proportion of inappropriate sleep duration and risk of mortality, compared with young and middle-aged adults. Single-measured sleep duration has been associated with mortality, but the health effects of long-term sleep duration trajectories remain unknown. This study aimed to explore the prospective associations between sleep duration trajectories and all-cause mortality amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…However, positive dose-response associations within certain intervals have also been reported [ 57 ], which may be related to confounding by unmeasured disease or subclinical symptoms, but regrettably, these LS7 studies have found no threshold effect. Sleep duration has been found to have an inverse L-shaped association with the risk of all-cause mortality, with a threshold effect showing an optimal critical value of approximately 9 h [ 58 ]. Our study extended previous investigations by adding sleep indicators and found the optimal threshold based on a negative dose-response association between overall CVH score and risk of cancer and death.…”
Section: Discussionmentioning
confidence: 99%
“…However, positive dose-response associations within certain intervals have also been reported [ 57 ], which may be related to confounding by unmeasured disease or subclinical symptoms, but regrettably, these LS7 studies have found no threshold effect. Sleep duration has been found to have an inverse L-shaped association with the risk of all-cause mortality, with a threshold effect showing an optimal critical value of approximately 9 h [ 58 ]. Our study extended previous investigations by adding sleep indicators and found the optimal threshold based on a negative dose-response association between overall CVH score and risk of cancer and death.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, menopausal status is associated with a high risk of mood disorders. In women with no history of depression or anxiety, perimenopausal and postmenopausal phases were associated with an increased risk of anxiety symptoms compared to premenopausal periods [26,[80][81][82][83][84][85][86].…”
Section: Menopausementioning
confidence: 95%
“…However, to the best of our knowledge, no study has investigated the potential impact of neighborhood levels of light and noise at night on sleep health in low-income and minoritized populations, which has limited our understanding of the impact of environmental exposures on long-term sleep health. Studying and understanding environmental determinants of long-term sleep trajectories helps to identify high-risk populations, uncover contributors to adverse health outcomes, and guide interventions [ 5 , 12 , 25 ].…”
Section: Introductionmentioning
confidence: 99%